Information Security and Cryptology - ICISC 2014 17th International Conference, Seoul, South Korea, December 3-5, 2014, Revised Selected Papers - Lee, Jooyoung; Kim, Jongsung; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2015)
This book constitutes the thoroughly refereed post-conference proceedings of the 17th International Conference on Information Security and Cryptology, ICISC 2014, held in Seoul, South Korea in December 2014. The 27 revised full papers presented were carefully selected from 91 submissions during two rounds of reviewing. The papers provide the latest results in research, development and applications in the field of information security and cryptology. They are organized in topical sections on RSA security, digital signature, public key cryptography, block ciphers, network security, mobile security, hash functions, information hiding and efficiency, cryptographic protocol, and side-channel attacks.
General Bounds for Small Inverse Problems and Its Applications to Multi-Prime RSA -- On the Security of Distributed Multiprime RSA -- Formal Modeling of Random Oracle Programmability and Verification of Signature Unforgeability Using Task-PIOAs -- Algebraic Cryptanalysis of Yasuda, Takagi and Sakurai$1 (Bs Signature Scheme -- Discrete Logarithms for Torsion Points on Elliptic Curve of Embedding Degree 1 -- Efficient Key Dependent Message Security Amplification Against Chosen Ciphertext Attacks -- A Fast Phase-Based Enumeration Algorithm for SVP Challenge Through y-Sparse Representations of Short Lattice Vectors -- How Much Can Complexity of Linear Cryptanalysis Be Reduced? -- Format-Preserving Encryption Algorithms Using Families of Tweakable Blockciphers -- Bicliques with Minimal Data and Time Complexity for AES -- Fault Analysis on SIMON Family of Lightweight Block Ciphers -- A Clustering Approach for Privacy-Preserving in Social Networks -- Securely Solving Classical Network Flow Problems -- Remote IP Protection Using Timing Channels -- Detecting Camouflaged Applications on Mobile Application Markets -- WrapDroid: Flexible and Fine-Grained Scheme Towards Regulating Behaviors of Android Apps -- A Collision Attack on a Double-Block-Length Compression Function Instantiated with Round-Reduced AES-256 -- LSH: A New Fast Secure Hash Function Family -- Lossless Data Hiding for Binary Document Images Using n-Pairs Pattern -- Montgomery Modular Multiplication on ARM-NEON Revisited -- A Fair and Efficient Mutual Private Set Intersection Protocol from a Two-Way Oblivious Pseudorandom Function -- Security Analysis of Polynomial Interpolation-Based Distributed Oblivious Transfer Protocols -- Compact and Efficient UC Commitments Under Atomic-Exchanges -- Issuer-Free Adaptive Oblivious Transfer with Access Policy -- Memory Address Side-Channel Analysis on Exponentiation -- Mutant Differential Fault Analysis of Trivium MDFA.s
Keywords: Computer science; Computer security; Data encryption (Computer science).; Management information systems; Computer Science; Systems and Data Security; Data Encryption; Management of Computing and Information Systems; Electronic books